ДОСЛІДЖЕННЯ ХАРАКТЕРИСТИК ПРЕЦІЗІЙНИХ ПІДСИЛЮВАЧІВ - Тесик, Ю.Ф.; Мороз, Р.М.; Туз, Ю.М.; Козир, О.В. (Інститут електродинаміки НАН України, Київ, 2020)
A review of the principles construction of existing high voltage measuring amplifiers (HVMA) was carried out. Their frequency range was investigated. It is proposed to use a circuit of additively connected operational amplifiers with virtual power to achieve the limiting frequencies of 400 kHz and a voltage of 500V. Several models of the circuit in the circuit simulator were investigated. It was found that to compensate for the phase shift of the output signal it is necessary to use boosting capacitances and a circuit with independent feedback. References 11, figures 5, table 3.